Factors contributing to and preventing mothers of children 1-6 aged from participating in the labour market in Kazakhstan - Kabylova, Moldir (2022)
Mothers of young children in Kazakhstan experience challenges to do paid work as the result of flaws in the state policies, motherhood penalty in the labor market and cultural barriers in the family institution. Absence of parental leave for fathers, three years unpaid maternity leave and shortage of state-subsidized childcare services reinforce traditional breadwinner family institution where women are the main caregiver and increase gender inequality. The labor market factors preventing mothers from fulfilling their fullest potential are wage gender gap, discrimination, and employers’ reluctance to hire women of reproductive age, and a lack of flexible work options. Within the family sphere, women in Kazakhstan spend three times more time on unpaid domestic work compared to men and mothers of young children are likely to have higher workload. The research aims to explore the main barriers preventing mothers of children 1-6 aged from participating in the labor market in Kazakhstan. The research applied the qualitative research method and conducted three focus group discussions among 15 mothers of young children residing in cities Almaty in Southern Kazakhstan. The results demonstrate that women face cultural and family barriers to do paid work in cosmopolitan Almaty and experience challenges to enter and remain in the labor market as a result of underdeveloped state policies and motherhood penalty in the labor market. Mothers of children 1-6 aged in Kazakhstan need sufficient number of childcare services for children aged under 3 subsidized by the state, flexible work schemes at workplace and policy incentives for fathers to take paternity leave